MODEL IMPLEMENTASI SILA KE 4 âKERAKYATAN YANG DIPIMPIN OLEH HIKMAT KEBIJAKSANAAN DALAM PERMUSYAWARATAN/ PERWAKILANâ SEBAGAI LOKUS PENDIDIKAN DEMOKRASI DI SMP KOTA SEMARANG - Suyahmo, Suyahmo (Jurnal Penelitian Pendidikan, 2015)
The purpose of this study was 1) the exploration Application Democ- racy Education in Junior Semarang; 2) What Weakness and Strength Application Democracy Education; 3) How to model Sila Implementation 4 as the locus of Democratic Education in Junior Semarang. The research method research approach and development (research and development). Location of the study will be selected from junior high schools that have implemented Democracy Education in Semarang. This research subject in addition to students, junior high school teacher in the city of Semarang. The results showed that (1) Implementation of democratic education in schools is carried out using a simulated election dominant class president and student council president directly. These conditions resulted in the student will understand that it is democratic. (2) In a democratic learning a lot of teachers who use the method of discussion, the conditions will be created to make studentsâ perception that the discussion is a method for developing a democratic character. (3) Many students found that dominant, apathetic, normal. Dominant conditions are not controlled by the teacher. (4) The Council is the original form of discussion Indonesia with special characteristics not shared by ordinary discussion.